Rate of broad-spectrum antibiotic overuse in patients receiving outpatient parenteral antibiotic therapy (OPAT) - Jessa R. Brenon; Stephanie E. Shulder; Sonal S. Munsiff; Colleen M. Burgoyne; Angela K. Nagel; Kelly E. Pillinger (Cambridge University Press, 2021)
Broad-spectrum antibiotics with once-daily dosing are often chosen for outpatient parenteral antibiotic therapy (OPAT) due to convenience even when narrower-spectrum antibiotics are appropriate. At our institution, up to 50% of select broad-spectrum OPAT regimens had potential to be narrowed, highlighting the need to re-evaluate regimens for de-escalation prior to discharge.